The Effect of Work Design Characteristics and Psychological Capital on Work Engagement - Reni Farida Yanti; Sri Suwarsi; Tasya Aspiranti (Institute of Computer Science (IOCS), 2022)
In public service institutions, such as the Regional Development Planning Agency (BAPPEDA) of Tasikmalaya Regency, aspects of work design characteristics and psychological capital support the emergence of positive behaviour so that employees will show a more positive attitude in carrying out their work. Based on the data obtained, it was found that the employees of BAPPEDA Tasikmalaya Regency had a good level of self-efficacy, as evidenced by the exposure of employees who believed in their abilities and liked challenging work for the development of their potential. In addition, employees also express self-confidence to achieve success in their current work. This employee's self-capacity can affect the level of work engagement of employees. The findings of work design characteristics problems at BAPPEDA Tasikmalaya Regency are characterized by low employee work design characteristics, especially those based on differences in age and education and psychological capital problems at BAPPEDA Tasikmalaya Regency marked by low employee confidence in dealing with work problems. The research method used is regression analysis to assess the influence between variables. The population in this study were all employees of BAPPEDA Tasikmalaya Regency who had agreed to participate in the study. The research instrument uses a questionnaire of work design characteristics, psychological capital, and work engagement which will be filled out by respondents, namely all employees at BAPPEDA Tasikmalaya Regency. This research will use a multiple linear regression test. The results showed a positive effect of work design characteristics on work engagement and a positive influence of psychological capital on work engagement. Furthermore, it was found that work design characteristics and psychological capital simultaneously and significantly affect employee work engagement at BAPPEDA Tasikmalaya Regency.